2004
DOI: 10.1038/sj.ejcn.1601944
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference as a measurement of obesity in the Netherlands Antilles; associations with hypertension and diabetes mellitus

Abstract: Objectives: To evaluate waist circumference (WC) as a screening tool for obesity in a Caribbean population. To identify risk groups with a high prevalence of (central) obesity in a Caribbean population, and to evaluate associations between (central) obesity and self-reported hypertension and diabetes mellitus. Design: Cross-sectional. Setting: Population-based study. Subjects: A random sample of adults (18 y or older) was selected from the Population Registries of three islands of the Netherlands Antilles. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
0
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 21 publications
(31 reference statements)
4
25
0
3
Order By: Relevance
“…These results are in accordance with studies showing that increased body mass contributes to hypertension [32,33]. Also it is established that increased weight and body fat composition is associated with non-communicable diseases, particularly CVD and diabetes [34]. Such association is also reported in the present study, as the prevalence of all metabolic syndrome components namely hypercholesterolemia, hypertriacylglycerolemia, hyperglycemia, diabetes and central obesity as well as the prevalence of metabolic syndrome, were higher in hypertensive than in normotensive women.…”
Section: Discussionsupporting
confidence: 95%
“…These results are in accordance with studies showing that increased body mass contributes to hypertension [32,33]. Also it is established that increased weight and body fat composition is associated with non-communicable diseases, particularly CVD and diabetes [34]. Such association is also reported in the present study, as the prevalence of all metabolic syndrome components namely hypercholesterolemia, hypertriacylglycerolemia, hyperglycemia, diabetes and central obesity as well as the prevalence of metabolic syndrome, were higher in hypertensive than in normotensive women.…”
Section: Discussionsupporting
confidence: 95%
“…In this study, we found that waist gain is associated with most MetS parameters, mainly with high levels of TGs and reduced levels of HDL-C and increased BP, as markedly observed in the literature (Carr et al, 2004;Grievink et al, 2004;Chuang et al, 2006;Menke et al, 2007;Hirani et al, 2008). On the other hand, in this study, entering FBS as a variable into analysis did not show any significant relationship with waist gain in both genders, as observed in some studies (Palaniappan et al, 2004;Stolk et al, 2005), possibly indicating a lower interference of waist gain in increases in FBS; however, some other studies showed inconsistent results (Nyamdorj et al, 2009;Sone et al, 2009).…”
supporting
confidence: 61%
“…Major indicators in this context are abdominal circumference 7,22 -which would provide a measure especially of visceral fat -and the body mass index (BMI), obtained by dividing weight in kilograms by the square of height in meters, which would refl ect the proportion of adipose tissue in the total body mass, regardless of localization. 2,4,11 Studies attempting to compare the associations with BMI and abdominal circumference have arrived at confl icting conclusions.…”
Section: Introductionmentioning
confidence: 99%